High incidence of Zika virus infection detected in plasma and cervical cytology specimens from pregnant women in Guayaquil, Ecuador. (February 2017) - Zambrano, Hector; Waggoner, Jesse; León, Karina; Pinsky, Benjamin; Vera, Ketty; Schettino, Marissa; Rivera, Lisette; Landivar, José; Granda, María; Lee, Angela; Mor, Gil
Abstract : Zika virus (ZIKV) infection during pregnancy has been linked to severe birth defects, and the epidemiologic situation of the ZIKV epidemic in Ecuador is poorly understood. Guayaquil, Ecuador, has a tropical climate and experiences frequent outbreaks of dengue and chikungunya virus, and in December 2015, ZIKV was identified. Given the well‐documented effects of ZIKV in pregnancy, including microcephaly, we tested for the presence of ZIKV in both plasma and cervical cytology of pregnant women. We report the identification of a population of pregnant women with a high incidence of ZIKV infection detected in the plasma and lower reproductive tract. A case‐control study was performed to determine the incidence of ZIKV infection among low‐income, pregnant women at risk for preterm delivery compared to matched controls. Plasma and cervical cytology specimens were tested for ZIKV by rRT‐PCR. Fifty‐nine pregnant women were enrolled. The incidence of ZIKV was 54% (32/59) overall: 18/31 (58.1%) in cases and 14/28 (50.0%) in controls. ZIKV detection in plasma and cervical cytology specimens demonstrated good agreement. Overall, outcomes for neonates born to ZIKV‐positive and ZIKV‐negative mothers were similar. However, two neonates were born with microcephaly to case mothers who were ZIKV positive. We report a high incidence of ZIKV infection (54%) in a distinctive population in Guayaquil, Ecuador. We identify ZIKV in cervical samples that correlates with ZIKV in the plasma. These data raise concerns regarding the breadth of the ZIKV epidemic in Ecuador and demonstrate the utility of cervical cytology specimens for ZIKV testing.